Tradisi Slametan Jawa dalam Perpektif Pendidikan Islam - Ainur Rofiq (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2019)
Each village must have a different tradition, culture, or habits. The tradition is also a local wealth owned by the nation, must always be maintained, preserved and also maintained so that the tradition is not extinct. No exception traditions that exist in the land of Java so much, such as the slametan tradition, both in the context of slametan event of pregnancy, marriage, circumcision or slametan tradition of death. Each has a certain way of doing it, although there are also some who have the same way. The Javanese slametan tradition in particular is the same as alms in the context of the Arabic language. So in a number of propositions both sourced from the Qur'an and the hadith are not explained in detail so that each region has a way and form a particular dish, so is not same between the form of dishes in East Java with Central Java, and so forth. Why is that, because this is influenced by the topography, history and also the hierarchy of each region. However, the context is the same magnitude that is almsgiving but the form is different. So in this case there is no need to debate between alms and slametan.